Left Atrial Remodeling is Associated with Left Ventricular Remodeling in Patients with Reperfused Acute Myocardial Infarction - Papadopoulos, Christodoulos E.; Zioutas, Dimitrios G.; Charalambidis, Panagiotis; Boulbou, Aristi; Triantafyllou, Konstantinos; Baltoumas, Konstantinos; Karvounis, Haralambos I.; Vassilikos, Vassilios (Journal of Cardiology and Cardiovascular Medicine, 2016)
Background: Left atrial volume (LAV) has been established as a sensitive marker of left ventricular (LV) diastolic function and as an independent predictor of mortality in patients with acute myocardial infarction (AMI). LA remodeling and its determinants in the setting of AMI have not been much studied. Methods: We studied 53 patients with anterior AMI and a relatively preserved LV systolic function, who underwent complete reperfusion and received guidelines guided antiremodeling drug management. LA and LV remodeling were assessed using 2D echocardiography at baseline and 6 months. LAV indexed for BSA (LAVi) was used as the index of LA size and further LA remodeling. Results: LAVi increased signifi cantly at 6 months compared to baseline [28.1 (23.0-34.5) vs 24.4 (19.5- 31.6) ml/m2, p=0.002] following LV end diastolic-volume index change [56.8 (47.6-63.9) vs 49.5 (42.0-58.4) ml/m2, p=0.0003]. Other standard LV diastolic function indices did not show any signifi cant change. Univariateanalysis showed a strong positive correlation of LAVi change with BNP levels at discharge, LV mass index and LV volumes indices change, throughout the follow up period. Multivariate regression analysis revealed that BNP plasma levels was the most important independent predictor of LA remodeling (b-coef.=0.630, p=0.001). Conclusions: Despite current antiremodeling strategies in patients with AMI, LA remodeling is frequently asssociated with LV remodeling. Additionally LAVi change in the mid-term reflects better than standard echocardiographic indices LV diastolic filling impairment.